VIRTUAL COMMUNITY OF PRACTICE FOR LOCAL DEVELOPMENT: DIVERSE CONTEXT AND PARTNERSHIP FOR ELEARNING IN PROJECT MANAGEMENT - Katernyak, Ihor; Loboda, Viktoriia; Strotskyy, Ruslan; Мamatova Тetiana (Socio-economic relations in the digital society, 2023)
The purpose of this paper is to generate an in-depth and comprehensive understanding of knowledge management processes in the virtual Community of Practice (vCoP) and to propose a framework for organising an eLearning process in project management for local development. The vCoP was created on the web platform for exchanging best practices and learning within a group of professionals with specific experiences and diverse learning needs. For 10 years, the vCoP annually brought together from 600 to 1,000 participants from different regions and organisations who defined problems, learned from the experience of others, took e-courses, worked in the virtual common space on developing project concepts, and prepared together a wide “repertoire” of new knowledge. The paper presents a study of operational processes of knowledge management in the vCoP and is based on primary datasets obtained within the period of 2018-early 2022 in terms of a joint domain, participatory membership and sense of community, knowledge sharing and learning, action, and construction of new knowledge. We present the findings of a study where the hypothesis was a combination of Community of Practice and eLearning into one system in order to quickly comprehend the problem that corresponds to the crisis, find solutions to the problem, and understand the benefits of their implementation while actively communicating with potential customers, and present project concepts to potential stakeholders, partners, and investors in order to mobilise resources. Given the challenges that Ukraine and partner countries are currently overcoming, in the post-war period, the proposed CoP approach based on a web platform can be used for creating public-private partnerships, for ensuring public participation in governance, in particular, for testing the efficiency of the ideas included in strategies and corresponding portfolios of programmes and projects to ensure resilience, revitalisation and development of territories and communities.